MiR-30e-5p deficiency exerts an inhibitory effect on inflammation in rheumatoid arthritis via regulating Atl2 expression - Shanshan Liu*; Kai Wang*; Ju Li; Yan Liu; Zhongyuan Zhang; Deqian Meng (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate the inflammatory effect of the microRNA (miRNA) miR-30e-5p on rheumatoid arthritis (RA) development in RA mice and fibroblast-like synoviocytes (FLS). Materials and methods: MiR-30e-5p and atlastin GTPase 2 (Atl2) expression in RA tissues and RA-FLS was evaluated using real-time quantitative polymerase chain reaction. The function of miR-30e-5p in inflammation of RA mice and RA-FLS was analyzed by enzyme-linked immunosorbent assay (ELISA) and Western blotting. 5-ethynyl-2ˊ-deoxyuridine (EdU) assay was used to detect RA-FLS proliferation. Luciferase reporter assay was to confirm the interaction between miR-30e-5p and Atl2. Results: MiR-30e-5p expression was upregulated in the tissues from RA mice. Silencing miR-30e-5p alleviated inflammation in RA mice and RA-FLS. MiR-30e-5p negatively modulated Atl2 expression. Atl2 knockdown exerted a proinflammatory effect on RA-FLS. Atl2 knockdown rescued the inhibitory effect of miR-30e-5p knockdown on proliferation and inflammatory response of RA-FLS. Conclusion: MiR-30e-5p knockdown inhibited the inflammatory response in RA mice and RA-FLS through Atl2.